IMPLEMENTASI MODEL PROBLEM BASED LEARNING PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS V SEKOLAH DASAR - Zaitun; Linda Zakiah; Yurniwati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the implementation of the Problem Based Learning (PBL) model in Pancasila Education learning with the material